2013
DOI: 10.11118/actaun201361051279
|View full text |Cite
|
Sign up to set email alerts
|

Resolving browning during the establishment of explant cultures in Vicia faba L. for genetic transformation

Abstract: Optimisation of in vitro regeneration systems of two explant types for low-tannine cultivars of faba bean based on culturing of shoot apices and cotyledonary nodes were provided by usage of various antioxidants -ascorbic acid, citric acid, glutathione and activated charcoal. In subsequent testing, the combined eff ects of antioxidants with transformation co-cultivation compounds acetosyringone and L-cysteine was studied. The application of antioxidants lead to decreased callogenesis, citric acids treatments (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Therefore, the results confirmed that if the quantity of oxidants in plantlets is diluted or reduced, there is no need to use antioxidants like ascorbic acid, glutathione citric acid etc. as has been reported by Abdelwahd et al (2008) and Klenotičova et al (2013), for reducing browning in broad bean.…”
Section: Black Sea Journal Of Agriculturesupporting
confidence: 85%
“…Therefore, the results confirmed that if the quantity of oxidants in plantlets is diluted or reduced, there is no need to use antioxidants like ascorbic acid, glutathione citric acid etc. as has been reported by Abdelwahd et al (2008) and Klenotičova et al (2013), for reducing browning in broad bean.…”
Section: Black Sea Journal Of Agriculturesupporting
confidence: 85%
“…It is generally considered as safe by the Food and Drug Administration because it has no association with health hazards (Tahjib-Ul-Arif et al, 2021). Many studies revealed that CA works as a chelating agent which bond with ions that are responsible for oxidation of polyphenol, and reduce accumulation of peroxidase, which scavenges reactive oxy- gen species (ROS) (Klenotic ˇová et al, 2013;Titov et al, 2006). CA has been reported to show conflicting results among different plant species and explants types.…”
Section: Discussionmentioning
confidence: 99%
“…CA has been reported to show conflicting results among different plant species and explants types. For example, it was reported to successfully reduce phenol browning in Vicia faba meristem culture (Klenotic ˇová et al, 2013), but it did not result in any change in the browning percentage of pomegranate cv. Ganesh from nodal segments (Singh and Patel, 2016) and resulted in more browning from axillary buds culture of Eucalyptus tereticornis (Sharma and Ramamurthy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other legumes, also in garden pea ( Pisum sativum ), first transformed in the late 1980, meristems have been the explants of choice, but the transformation protocols have been gradually improved and successfully employed for various purposes, although a strong genotypic effect has been shown ( Klocke et al, 2010 ; Mikschofsky and Broer, 2012 ). The broad bean ( Vicia faba ) is probably one of the most difficult legume species to regenerate and transform, requiring particular efforts to solve the problem of tissue blackening in vitro ( Klenotičová et al, 2013 ), and only few successful experiments have been reported using Agrobacterium-mediated transformation of meristematic cells or stem segments [reviewed in ( O’Sullivan and Angra, 2016 )]. Due to the intrinsic difficulties of legume regeneration systems, a range of methods not requiring tissue culture of explants have been proposed ( Somers et al, 2003 ), including the electroporation of nodal axillary buds in pea and cowpea ( Chowrira et al, 1996 ), the Agrobacterium inoculation of germinating seeds in pea and bean ( Liu et al, 2005 ; Svabova et al, 2005 ), the inoculation of flower buds in cowpea ( Ilori and Pellegrineschi, 2011 ).…”
Section: Regeneration and Transformationmentioning
confidence: 99%